Planning for the Implementation of the Electronical Neighborhood Unit Application: Planning for the Implementation of the Electronical Neighborhood Unit Application - Zuraidah, Eva; Jorddy, Jorddy (Politeknik Ganesha Medan, 2019)
Along with developments, times, digital technology is growing and all activities will be carried out online because it is considered more practical and fast, and saves time. A neighborhood association is a community organization consisting of several residents and heads of households who have family cards (KK) that are domiciled in the neighborhood (RT) in one environment. Activities in the neighborhood include taking care of the boarding house domicile (stay report), making an electronic letter of identity card to the neighborhood residents (RW), making a domicile letter and providing information to residents, making a death certificate, moving a house. Sometimes the activities in the neighborhood also require quite a long time and the process is less efficient. For this purpose, an e-government-based website was designed for the neighborhood of the neighborhood called the electronic neighborhood association (RT). Neighborhood association electronics (E-Rt) is a website that is intended for residents in the community, namely to access activities in neighborhood neighborhoods. Making E-RT using Php Mysql and using the waterfall methodology